PREHOSPITAL CARE: CHALLENGES OF THE EMERGENCY MOBILE CARE SERVICE FROM THE VIEWPOINT OF NURSES (Fiep Bulletin - online, 2014)
Objective: Analyze the main challenges faced in prehospital care (PHC), from the viewpoint of nurses. Methodology: Exploratory research, with a qualitative approach, carried out in the Emergency Mobile Care Service (SAMU) in the town of Cajazeiras, Paraíba, Brazil. The sample consisted of 16 nurses, among them 1 coordinator. Data collection took place in October and November 2012, using a questionnaire, after approval by the Research Ethics Committee of Faculdade Santa Maria, under the Protocol 126,837. The analysis was performed using the Content Analysis technique proposed by Bardin. Results: Participants discreetly expressed the way how they deal with challenges faced in PHC and this was identified by means of the following categories: Main challenges faced by the nurse with regard to PHC; Challenges faced in PHC which may affect the care provided to the victim; Relation of the SAMU team to the services supporting PHC; Aspects in which SAMU must improve to provide a better care. Final remarks: We found out that there is a need for further studies on this theme, in order to provide an adequate knowledge on the subject, given the small number of publications available in this area.
Keywords: Pre-hospital care; Emergency Mobile Care Service; Nursing.